ANALISIS PENGARUH REPUTASI HOTEL TERHADAP MINAT MELAMAR PRAKTEK KERJA LAPANGAN MAHASISWA - Victor Bangun Mulia (Kepariwisataan: Jurnal Ilmiah, 2021)
Internship programs, especially in 5-star hotels that are reputable with the best standards, can be a strong bridge for students to be able to apply the knowledge gained at the institution into the world of work. With a wide choice of high-standard and reputable hotels provided by the campus, it was not fully welcomed by students who would go to the internship program. There are also many students who do not send applications or even reject the contract proposed by the hotel when he has successfully carried out an interview session at the hotel. This study aims to find a picture of students' perceptions of hotel reputation and interest of students in applying for internships also to see the effect of hotel reputation on students' interest in applying. The method used is descriptive statistics and simple linear regression analysis. Questionnaires were distributed to 40 students. The results of this study found that hotel reputation affects interest in applying for internship by 48.6% while the rest is influenced by other factors which are not explained in this study. In addition, the most important aspect of hotel reputation according to students is hotel products and services. The majority of students tend to make their own decisions for the position they are applying for according to their interests and talents.Keywords: Internship; Hospitality; Student; Reputation